1968
DOI: 10.1017/s000335610002609x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of level of feeding of sows during pregnancy. III. Body composition

Abstract: 1. Four groups of three litter-sister Large White gilts were given during four successive pregnancies a daily meal allowance of either 2·70 kg (High), 1·35 (Low) or 1·35 kg for 76 days followed by 2·70 kg until parturition (Low-High). During 8-week lactation periods all received the same daily allowance of 1·8 kg meal plus 0·35 kg for each piglet suckled.2. On the 100th day of the fourth pregnancy all sows were slaughtered. The major internal organs were weighed and measurements recorded of the length of carca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1972
1972
2001
2001

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Comparing the values with those found by Whittemore et al (1980), the present gilts were fatter at mating when judged by ultrasonic observations but not so when the depths were corrected to carcass values. The thickness of the skin alone in parity 3 sows on low food intakes approaches 10 mm (Elsley, MacPherson and Lodge, 1968), indicating a value close to zero for the thickness of subcutaneous adipose tissue for sows on treatment A at the termination of the present experiment. At equivalent energy intakes during gestation in the present experiment, there would probably have been an increase in depth of fat due partly to the shorter lactation.…”
Section: Resultsmentioning
confidence: 53%
“…Comparing the values with those found by Whittemore et al (1980), the present gilts were fatter at mating when judged by ultrasonic observations but not so when the depths were corrected to carcass values. The thickness of the skin alone in parity 3 sows on low food intakes approaches 10 mm (Elsley, MacPherson and Lodge, 1968), indicating a value close to zero for the thickness of subcutaneous adipose tissue for sows on treatment A at the termination of the present experiment. At equivalent energy intakes during gestation in the present experiment, there would probably have been an increase in depth of fat due partly to the shorter lactation.…”
Section: Resultsmentioning
confidence: 53%
“…Elsley, MacPherson and Lodge (1968) found that at low intake levels weight losses occurred, accompanied by depletion in subcutaneous fat levels, and concluded that continued depletion of reserves must lead to reduced reproductive performance. Elsley, MacPherson and Lodge (1968) found that at low intake levels weight losses occurred, accompanied by depletion in subcutaneous fat levels, and concluded that continued depletion of reserves must lead to reduced reproductive performance.…”
Section: Discussionmentioning
confidence: 99%
“…The skin of non-pregnant gilts could be expected to be about 3% of carcass weight (Hill and O'Carroll, 1962), and that of sows 9-5 to 11-5% of carcass weight (Elsley et al, 1968). In particular the weight of subcutaneous fat+skin had been halved.…”
Section: Discussionmentioning
confidence: 99%